Pengaruh Orientasi Posisi Printing Z Axis Mesin 3D Printing Terhadap Kuat Tarik Menggunakan Filamen Super Tough PLA - Hasdiansah Hasdiansah; Pristiansyah Pristiansyah; Zaldy S Suzen (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
The manufacture of the main parts of a mechanical system can use 3D Printing technology. One of the cheapest 3D printing technologies is using Fused Deposition Modeling (FDM). There are many materials that can be printed with FDM technology such as PLA, Super Tough PLA, ABS, Nylon, PETG, and others. The more expensive FDM technology, the more types of filaments that the machine can print. The ASTM D638 Type IV standard tensile test specimen is often used by researchers to see the tensile strength of printed products. This study uses several process parameters that are set in the slicing software which are then in the form of G-Code and stored in an SD card and processed on the FDM 3D Printer machine. The ST-PLA filament used in this study is 1.75 mm in diameter and uses a 0.4 mm nozzle. The process parameters set in the slicing software are as follows nozzle temperature 195°C, bed temperature 60°C, travel speed 120 mm/s, default printing speed 50 mm/s, layer thickness 0.3 mm, internal fill pattern wiggle, external fill pattern concentric, bottom layer 5, top layer 5, and perimeter 5. Variables that change in the orientation of the print position or Z Rotate Degree 0°, 5°, 10°, 15°, 20°, 25°, 30°, 35°, 40°, 45°, 50°, 55°, 60°, 65°, 70°, 75°, 80°, 85°, and 90°. The highest value of the tensile strength test results for the standard ASTM D638 Type IV test specimen was obtained in experiment number twelve (12) which was 61.10 Mpa with a rotating angle of the Z axis of 55° seven (7) which is 37.50 MPa. The influence of the orientation of the Z-axis rotation angle on the required filament weight in the tensile test specimen printing process is not significant, which is only 0.01 gram.